WebGIS sebagai media diseminasi kemas ulang informasi - Nurida Maulidia Rahma (Berkala Ilmu Perpustakaan dan Informasi, 2020)
Introduction. Not all scientific work can be easily utilized directly by the public (society). Pusat Data dan Dokumentasi Informasi Ilmiah (PDDI) has not optimally disseminated knowledge products. The knowledge products should be assembled, visualized and informed - through digital media. This paper aims to examine whether WebGIS can be used as a medium for disseminating information. Data Collection Method. The method used was descriptive qualitative. Data collection was conducted by means of a survey. Data Analysis. This research use descriptive analysis. The results of the survey analysis were reviewed with the results of literature studies so that conclusions could be drawn to answer the research questions. Results and Discussions. The survey shows that the Banyuwangi community expect that an interactive industrial tree to be attached in the WebGIS (BAGEOS) of the Banyuwangi Regency Government. The survey shows that installing industrial trees on BAGEOS is not only beneficial for BAGEOS, but also for the community. Conclusions. Combination between industrial trees with WebGIS or digital maps is a good combination. All respondents agreed to pair industrial trees on digital maps. GIS is capable as a medium for disseminating information packaging.